Miller's guide to the dissection of the dog - Evans, Howard E. (W. B. Saunders Company, 1971)
This book walks readers through the dissection of every area of a dog's anatomy. It is the only resource that explains and illustrates exactly where to cut and what to look for. Over 250 illustrations--the most detailed available in any text--depict each dissection procedure step by step